Simultaneous Dual Recordings From Vestibular Hair Cells and Their Calyx Afferents Demonstrate Multiple Modes of Transmission at These Specialized Endings - Contini, Donatella; Holstein, Gay R.; Art, Jonathan J. (Frontiers in Neurology, 2022)
In the vestibular periphery, transmission via conventional synaptic boutons is supplemented by post-synaptic calyceal endings surrounding Type I hair cells. This review focusses on the multiple modes of communication between these receptors and their enveloping calyces as revealed by simultaneous dual-electrode recordings. Classic orthodromic transmission is accompanied by two forms of bidirectional communication enabled by the extensive cleft between the Type I hair cell and its calyx. The slowest cellular communication low-pass filters the transduction current with a time constant of 10–100 ms: potassium ions accumulate in the synaptic cleft, depolarizing both the hair cell and afferent to potentials greater than necessary for rapid vesicle fusion in the receptor and potentially triggering action potentials in the afferent. On the millisecond timescale, conventional glutamatergic quantal transmission occurs when hair cells are depolarized to potentials sufficient for calcium influx and vesicle fusion. Depolarization also permits a third form of transmission that occurs over tens of microseconds, resulting from the large voltage- and ion-sensitive cleft-facing conductances in both the hair cell and the calyx that are open at their resting potentials. Current flowing out of either the hair cell or the afferent divides into the fraction flowing across the cleft into its cellular partner, and the remainder flowing out of the cleft and into the surrounding fluid compartment. These findings suggest multiple biophysical bases for the extensive repertoire of response dynamics seen in the population of primary vestibular afferent fibers. The results further suggest that evolutionary pressures drive selection for the calyx afferent.